2014
DOI: 10.1037/a0034282
|View full text |Cite
|
Sign up to set email alerts
|

Modeling continuous self-report measures of perceived emotion using generalized additive mixed models.

Abstract: Emotion research has long been dominated by the "standard method" of displaying posed or acted static images of facial expressions of emotion. While this method has been useful, it is unable to investigate the dynamic nature of emotion expression. Although continuous self-report traces have enabled the measurement of dynamic expressions of emotion, a consensus has not been reached on the correct statistical techniques that permit inferences to be made with such measures. We propose generalized additive models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 78 publications
0
44
1
Order By: Relevance
“…One solution is to compensate for the inherent ambiguity in affect annotation using multilabel classification techniques (not to be confused with multi-class classification [75]) where multiple viewpoints on the same affective state can co-exist. Another is to attempt to increase reliability and the simplest way to do this is to increase the number of observers [9,52]. Or perhaps, it might be advisable to consider both options.…”
Section: Main Findings and Implicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…One solution is to compensate for the inherent ambiguity in affect annotation using multilabel classification techniques (not to be confused with multi-class classification [75]) where multiple viewpoints on the same affective state can co-exist. Another is to attempt to increase reliability and the simplest way to do this is to increase the number of observers [9,52]. Or perhaps, it might be advisable to consider both options.…”
Section: Main Findings and Implicationsmentioning
confidence: 99%
“…The basic intuition is that the easiest way to increase reliability is to simply increase the number of observers so that observer-specific variance gets cancelled out. McKeown and Sneddon [52] performed a simulated analysis and concluded that 20-30 observers were needed to confidently detect an emotional signal from time-continuous annotations. Although they are careful to make no claims on generalizability of this result to other situations 2 , requiring such a large number of observers might not always be feasible.…”
Section: Iterative Annotation Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…According to McKeown and Sneddon [2014], the standard method for annotating data is to have fixed and known time segments associated with a descriptive label. In our system, agent events deliver start and end boundaries automatically, as they are triggered by the interaction modeling component.…”
Section: Event-based Annotationmentioning
confidence: 99%